Copyright : what everyone needs to know - Netanel, Neil (What everyone needs to know., 2018)
In Copyright: What Everyone Needs to Know®, intellectual property expert Neil Weinstock Netanel guides readers through the murky dynamics of modern copyright law. From the basis and purpose of copyright law to a glimpse at what the law could - or should - become in the digital age, Netanel offers the necessary tools for understanding the recent controversies about copyright.